Inklusisme Islam dalam Memahami Fenomena Kemanusiaan - Barizi, Ahmad (el Harakah: Jurnal Budaya Islam, 1999)
Religion is a very important thing for its adherents who can easily be known and can also be seen. Increasingly magnificent mosques, religious party habits (especially Islam) are increasingly revealing as the reform era, which in turn is marked by the plurality of religious symbolism of society, is an outward appearance that is easily visible and seems unnecessarily disputed. Humans as the center of the formation of Islamic teachings is demanding the creation of human religious inclusivism on earth. This conception of religious inclusivism will be created in human civilization dynamically and harmoniously when the universal consciousness of human brotherhood is formed. The conception of inclusivism as the articulation of plural and pluralistic human phenomena is essentially expected to give birth to the concept of the unity of mankind (universal humanity, ummatan wahidah). Agama merupakan hal yang sangat penting bagi para pemeluknya yang dengan mudah dapat diketahui dan bisa juga dilihat. Masjid yang semakin megah, keberbagaian partai agama (terutama Islam) yang kian menguak akibat retasnya era reformasi, yang pada gilirannya ditandai dengan pluraritas simbolisme keagamaan masyarakat, ini merupakan wujud luar yang mudah kelihatan dan tampaknya tak perlu diperdebatkan. Manusia sebagai sentra terbentuknya ajaran Islam inilah menuntut terciptanya inklusivisme keagamaan manusia di muka bumi. Konsepsi inklusivisme keagamaan ini akan tercipta dalam peradaban manusia secara dinamis dan harmonis bila kesadaran pesaudaraan manusia secara universal sudah terbentuk. Konsepsi inklusivisme sebagai artikulasi terhadap fenomena- fenomena manusiawi yang sangat plural dan majemuk pada esensinya diharapkan melahirkan konsep tentang kesatuan umat manusia (kemanusiaan universal, ummatan wahidah).